ANALISIS VARIANS BIAYA OPERASIONAL DALAM MENGUKUR EFEKTIVITAS PENGENDALIAN BIAYA OPERASIONAL PADA KANTOR WILAYAH VI PT.PEGADAIAN (PERSERO) MAKASSAR - Rustan Rustan; Muttiarni Muttiarni; Idra Wahyuni (Jurnal Riset Perpajakan: Amnesty, 2019)
Research aims to determine the effective measurement of operational cost control of variance operational cost in regional office VI PT. Pegadaian (Persero) Makassar.  The approach used in this research is a qualitative approach. The research object is located in regional office VI PT. Makassar pawnshop (Persero) with the address Jl. Kumala Raya No. 7, Makassar, South Sulawesi 90223. The types of data used in this research are qualitative data, while the source of data obtained in this research is a secondary source. The data analysis methods used to test the hypothesis are using descriptive methods and analysis of the variance of operational costs. The results of this research show that in 2015 the realization of the cost of Rp 233.361.221. Exceeds the budget of the stipulated cost (unfavorable) of Rp. 223.058.122. As for the year 2016 the realization of the cost of Rp. 280.772.516 not exceed From budget...